Exploring the theme. The poetic concept of “meaning” as light for the screenwriting process - Brenes, Carmen Sofía (2019)
This article deals with the concept of “meaning” developed by Juan José García- Noblejas in 1982, which is presented as an enlightening and useful tool for the screenwriting and film reception process. The essay explores the concepts of “theme” (Flinn, 1999:167-168); “dramatic question” (Selbo, 2007: 201-209); and “meaning” (Russin, 2012: 38-42) as they appear in screenwriting manuals from an academic point of view. Considering the perspectives of narratology, semiotics and Aristotelic Poetics the article relates the concept of “meaning” with the unifying principle of the story and the aspects of the human experience the story shows.